Palonosetron versus tropisetron with dexamethasone for prevention of postoperative nausea and vomiting in pediatric adenotonsillectomy: a single center, randomized controlled trial - Hualin Chen; Liping Sun; Jijian Zheng; Hongbin Gu (Frontiers in Medicine, 2025)
BackgroundPostoperative nausea and vomiting (PONV) remain significant complications following pediatric adenotonsillectomy. Although palonosetron, a second-generation 5-HT3 receptor antagonist, has shown potential for preventing PONV, further research is needed to assess its efficacy when combined with dexamethasone in pediatric otolaryngologic procedures. This study aims to observe the efficacy of palonosetron or tropisetron combined with dexamethasone in preventing PONV in children undergoing adenotonsillectomy.MethodsWe enrolled 110 children scheduled for elective adenotonsillectomy under general anesthesia. Based on a computer-generated random number table, children were assigned in equal proportions to receive either palonosetron or tropisetron. The P-group received palonosetron (1 μg/kg, maximum 50 μg), while the T-group received tropisetron (0.1 mg/kg, maximum 2 mg) 5 min before anesthesia induction. After receiving their allocated drug, children received intravenous dexamethasone (0.15 mg/kg, maximum 5 mg) during induction. Primary outcomes included PONV incidence at 6, 24, and 48 h postoperatively. Secondary outcomes included the number of children with PONV scores of 1, 2, and 3, rescue antiemetic medication, and adverse events.ResultsA total of 110 children (aged 3–12 y, ASA physical status 1 or 2, weighted 14.3–47.3 kg) were enrolled in the study between December 2021 and July 2023. The P-group (n = 52) demonstrated significantly lower PONV incidence than the T-group (n = 51) during the 0–48 h (5.8% vs. 25.5%, p < 0.05). Notably, this difference was most pronounced during the first 24 h: 0–6 h (0% vs. 10%, p < 0.05) and 6–24 h (3.8% vs. 7.8%, p < 0.05). The difference during 24–48 h was insignificant (4% vs. 8%, p > 0.05). Transient junctional rhythm occurred in three patients receiving tropisetron, which did not affect circulation. Headache and dizziness were similar between groups within 48 h (P-group: 3.8%, T-group: 7.8%, p > 0.05).ConclusionIn pediatric adenotonsillectomy, palonosetron with dexamethasone gives better PONV prevention than tropisetron with dexamethasone, especially in the first 24 h, with comparable safety.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=127115, ChiCTR2100046848.